RADT-03. OUTCOMES OF PATIENTS WITH HER2-POSITIVE BREAST CANCER METASTATIC TO BRAIN TREATED WITH HER2-TARGETED SYSTEMIC THERAPY AND STEREOTACTIC RADIOSURGERY. (12th November 2021) - Shumway, John; Torras, Marina; Reeder-Hayes, Katherine; Jolly, Trevor; Dees, Elizabeth; Ray, Emily; Muss, Hyman; Carey, Lisa; Shen, Colette
Abstract: OBJECTIVE: For patients with HER2-positive breast cancer metastatic to brain, HER2-directed systemic therapies are increasingly used with stereotactic radiosurgery (SRS). These include monoclonal antibodies such as trastuzumab (H) and pertuzumab (P), antibody-drug conjugates such as ado-trastuzumab emtansine (T-DM1), and tyrosine kinase inhibitors such as lapatinib. Limited data exist regarding appropriate timing with SRS and outcomes of this treatment regimen. METHODS: A single-institution retrospective review collected clinical data on patients with breast cancer metastatic to brain who were treated with SRS from 2009-2020. Statistical analyses were performed using the Kaplan-Meier method and chi-square statistic. RESULTS: Of 82 patients with breast cancer metastatic to brain treated with SRS, 33 (40%) were HER2-positive, 18 of whom were hormone receptor-positive. At brain metastasis diagnosis, 15 patients (45%) had >1 intracranial metastasis (range 2-7), and the median brain metastasis maximal dimension was 2.0 cm. Fifteen patients had uncontrolled extracranial disease. After brain metastasis diagnosis, 9 patients (27%) were treated with systemic therapy first (T-DM1+/-HP, lapatinib+HP, chemotherapy+/-HP) followed by SRS at a median of 18.6 months after starting systemic therapy. Seven patients (21%) were treated with SRS first, followed by systemic therapy in 6 of these patients (multi-agent regimens, 4 including T-DM1 or lapatinib). Seventeen (52%) received concurrent systemic therapy and SRS (T-DM1+/-chemotherapy, lapatinib, HP, hormone therapy, chemotherapy). Median follow-up time was 21.1 months. Median overall survival was 24.8 months and not statistically different between treatment groups. Four patients (12%) developed symptomatic radionecrosis; 3 were on T-DM1 concurrent with SRS. CONCLUSION: In this small patient sample, we noted favorable survival outcomes for patients with HER2-positive breast cancer metastatic to brain when treated with HER2-targeted therapies together with SRS. The sequence of systemic therapy and SRS does not appear to impact survival outcomes. Concurrent treatment with T-DM1 and SRS may be associated with higher rates of radionecrosis.